2018
DOI: 10.3389/fmicb.2018.00757
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lactobacillus reuteri in Human Health and Diseases

Abstract: Lactobacillus reuteri (L. reuteri) is a well-studied probiotic bacterium that can colonize a large number of mammals. In humans, L. reuteri is found in different body sites, including the gastrointestinal tract, urinary tract, skin, and breast milk. The abundance of L. reuteri varies among different individuals. Several beneficial effects of L. reuteri have been noted. First, L. reuteri can produce antimicrobial molecules, such as organic acids, ethanol, and reuterin. Due to its antimicrobial activity, L. reut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
400
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 504 publications
(464 citation statements)
references
References 238 publications
9
400
0
9
Order By: Relevance
“…In addition, we have shown that L reuteri cell‐free supernatant was as effective in inhibiting P gingivalis as living bacteria, suggesting that microbial growth reduction was mainly due to the substances produced by the probiotic. Besides reuterin, L reuteri strains produce a series of other antimicrobial substances, including lactic acid, acetic acid, ethanol, and reutericyclin . The literature has also shown the importance of the acidic environment in the interactions between L reuteri and other microorganisms .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, we have shown that L reuteri cell‐free supernatant was as effective in inhibiting P gingivalis as living bacteria, suggesting that microbial growth reduction was mainly due to the substances produced by the probiotic. Besides reuterin, L reuteri strains produce a series of other antimicrobial substances, including lactic acid, acetic acid, ethanol, and reutericyclin . The literature has also shown the importance of the acidic environment in the interactions between L reuteri and other microorganisms .…”
Section: Discussionmentioning
confidence: 99%
“…The literature has also shown the importance of the acidic environment in the interactions between L reuteri and other microorganisms . Additional well‐studied metabolites such as histamine, vitamins, and exopolysaccharides contribute to L reuteri probiotic action and can be found in the culture supernatant . However, L reuteri metabolites are present in different concentrations in live bacterial suspension and in the supernatant, since special conditions of time and substrate addition (glycerol) were offered to the culture to prepare the supernatant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations